Fundus Autofluorescence and Spectral Domain OCT in Central Serous Chorioretinopathy. (8th August 2011) - Roisman, Luiz; Lavinsky, Daniel; Magalhaes, Fernanda; Aggio, Fabio Bom; Moraes, Nilva; Cardillo, Jose A.; Farah, Michel E.
Abstract : Background . To describe the standard autofluorescence (FAF), the near infrared autofluorescence (NIA) and optical coherence tomography (OCT) patterns in central serous chorioretinopathy, correlating them with fluorescein angiography. Methods . Cross-sectional observational study, in which patients with at least seven months of CSC underwent ophthalmologic examination, fundus photography, FAF, NIA, fluorescein angiography (FA), and spectral-domain OCT. Results . Seventeen eyes of thirteen patients were included. The presentation features were a mottled hyperFAF in the detached area and areas with pigment mottling. NIA images showed areas of hyperNIA similar to FAF and localized areas of hypoNIA, which correlated with the points of leakage in the FA. OCT showed pigment epithelium detachment at the location of these hypoNIA spots. Discussion . FAF showed increased presence of fluorophores in the area of retinal detachment, which is believed to appear secondary to lipofuscin accumulation in the RPE or the presence of debris in the subretinal fluid. NIA has been related to the choroidal melanin content and there were areas of both increased and decreased NIA, which could be explained by damage ahead the retina, basically RPE and choroid. These findings, along with the PEDs found in the areas of hypoNIA, support the notion of a primary choroidal disease in CSC.